THE EFFECT OF TEAMWORK AND FLEXIBLE WORK ARRANGEMENTS ON WORKFORCE AGILITY AT THE MAKASSAR CITY EDUCATION DEPARTMENT - Ahmad Raihan Al Bustani; Anwar Anwar; Tenri Sayu Puspitaningsih Dipoatmodjo (Universitas Negeri Makassar, 2026)
Abstract: This research aims to Analyzing the influence of teamwork and flexible work arrangements on workforce agility at the Makassar City Education Office.The variables in this study are teamwork and flexible work arrangements as independent variables and workforce agilityas the dependent variable. The population in this study was 154 Civil Servants at the Makassar City Education Office, while the sample was 111 Civil Servants at the Education Office. useSlovin formula assisted by SPSS 29. The data collection techniques used were observation and documentation. The data analysis techniques used were descriptive percentage analysis, instrument testing consisting of validity and reliability tests, hypothesis testing consisting of multiple linear regression analysis, t-test, F-test and coefficient of determination (r2). Based on the results of data analysis conducted at the Makassar City Education Office with 111 State Civil Apparatus, teamwork and flexible work arrangements have a positive and significant effect on Workforce Agility.Keywords: Teamwork, Flexible Work Arrangements, Workforce Agility.